Droop-multimode trade-off in GaN-InGaN LEDs: Effect of polarization-matched AlInGaN blocking layers. (December 2015) - Pendem, Vikas; Adhikari, Sonachand; Mathew, Manish; Singh, Sumitra; Pal, Suchandan
Abstract: Polarization-matched graded AlInGaN electron blocking layer (EBL) and hole blocking layer (HBL) are proposed to reduce efficiency droop in GaN-InGaN light-emitting diodes (LEDs). Five different structures have been simulated to study the effect of different blocking layers and a significant reduction in the efficiency droop has been noticed, from 52% in conventional structure to 2% in polarization-matched graded AlInGaN EBL and HBL structure at a current density of 1000 A cm −2 . This has been achieved at the cost of multimode emission from such polarization-matched blocking layers which sets a trade-off between efficiency droop and multimode emission. The AlInGaN layer can therefore be characterized by droop cut-off condition (DCC) and multimode cut-off condition (MCC). For the best structure proposed in this paper, simulations indicate a DCC having Al and In composition of 0.10 and 0.15 respectively; and an MCC having Al and In composition of 0.08 and 0.23 respectively. Highlights: Efficiency droop is reduced by polarization-matched graded AlInGaN EBL and HBL. Droop reduced from 52% to 2% measured at a current density of 1000 A cm −2 . A high-intensity secondary emission is observed due to AlInGaN blocking layers. A trade-off exists between efficiency droop and multimode emission.